Security+ study guide & DVD training system - Cross, Michael, 1965- (Burlington, MA : Syngress Pub., 2007)
Book and DVD-ROM cover all the CompTIA Security+ exam objectives.
Accompanying DVD-ROM includes a complete Adobe PDF format version of the print study guide, along with a complete practice exam with detailed answers and explanations. Fast Tracks for a quick topic review are provided in both HTML and PowerPoint format.
Περιέχει ευρετήριο.
Keywords: Computer networks -- Security measures -- Examinations, questions, etc; Electronic data processing personnel -- Certification -- Study guides